Effect of sterilization and irrigating solutions on nanostructure alteration of Ni-Ti rotary instruments in endodontics: An atomic force microscopic study - Izaz Shaik; Bhargavi Dasari; Satish Alapati; Padma C Dhavala; Rahul Tiwari; Heena Dixit Tiwari (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim: This study aimed to evaluate the effect of 5.25% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA) and sterilization on the nanostructural alteration of nickel titanium (Ni-Ti) rotary file systems in endodontics using the atomic force microscopy (AFM). Materials and Methods: The study was performed on four commercially available rotary Ni-Ti files: group I—Vortex Blue (Dentsply), group II—ProTaper Next (Dentsply), group III—Mtwo (VDW), and group IV—iRaCe (FKG). Each group was divided into four subgroups (n = 4), that is, subgroup A—control (new rotary file), subgroup B—subjected for five cycles of autoclave, subgroup C—immersed in 5.25% NaOCl for 5 minutes, and subgroup D—immersed in 17% EDTA solutions for 5 minutes. All the specimens were evaluated with AFM using roughness average (RA) and root-mean-square (RMS) values for surface roughness. Results: Among control groups, Vortex Blue showed the least RA and RMS values; the highest surface roughness was seen with Mtwo files. All the Ni-Ti rotary files showed a statistically significant (P <0.05) increase in surface hardness when subjected to autoclave and treatment with different irrigating solutions. In particular, 17% EDTA caused the highest surface deterioration in all the groups. Conclusion: AFM analysis revealed increased surface roughness values recorded for all the rotary files when treated with irrigating solutions and autoclave cycles.